THE STRATEGIES FOR LEARNING THE HISTORY OF ISLAMIC CIVILIZATION - Fithriy, Haniefa Nuruddienil; Sirojudin, Didin (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2021)
The limited allocation of time, which is only 2 hours per week, the curricula that often change, the stereotypes about the History of Islamic Civilization (Sejarah Kebudayaan Islam or SKI) as a merely complementary and a boring subject, are among significant obstacles for SKI teachers to deliver the learning of the subject with demands for changes in the students’ cognitive, affective, and psycho-motoric aspects,. This paper aims at studying the strategies employed by the SKI teacher at the Islamic Junior High School (Madrasah Tsanawiyah or MTs) “Bahrul Ulum” Gadingmangu – Perak – Jombang in learning the subject to the students. The study is qualitative field research and the data was analyzed using the descriptive method. The findings show that the teacher’s good preparation and mastery of the subject, the Small Group Work (SGW) technique, and self-habituation activities have helped much in overcoming obstacles in the SKI learning as well as helping students to obtain good achievement both academically and non-academically.